The in vitro effect of human polymorphonuclear leukocyte azurophil granule components on natural killer cell cytotoxicity - Lindemann, R A; Lala, A; Miyasaki, K T (Oral microbiology and immunology, 1994)
We previously demonstrated that human polymorphonuclear leukocyte (PMN) secretions are capable of activating and inhibiting natural killer cell (NK) cytotoxicity depending on the eliciting PMN stimulus. Serum-opsonized zymosan induced PMN to secrete substances that enhanced NK activity in vitro. Serum-opsonized zymosan stimulates the release of PMN azurophil granules, which contain both human neutrophil peptides (HNPs) and neutral serine proteases (NSPs). When HNPs and NSPs were tested for their ability to activate NK cells in peripheral blood lymphocytes, all but cathepsin G consistently enhanced cytotoxicity above control values. HNP-induced cytotoxicity was significantly enhanced within 12 h, peaking at approximately 24 h. Of the HNPs, HNP-1 was the most potent activator, enhancing NK activity at 1.25 micrograms/ml. Interleukin-2 and interferon-gamma were not involved in this activational process, as antibodies to interleukin-2 and interferon-gamma did not block activation by HNPs and NSPs, and interleukin-2 receptor expression was unaltered after 24 h of incubation. Enzymatically inactivated elastase and cathepsin G produced equivalent activational effects to their active counterparts. Antisera to elastase and cathepsin G decreased but did not eliminate NK activation over untreated peripheral blood lymphocytes. These data suggest that certain PMN azurophil granule components, including HNPs and NSPs directly increase the cytotoxic activity of NK cells.